Prevalence of iron deficiency in male elite athletes - Malczewska-Lenczowska, J.; Stupnicki, R.; Szczepanska, B. (Biomedical Human Kinetics, 2009)
Study aim: To assess the prevalence of iron deficiency in competitive male athletes. Material and methods: In total, 90 elite athletes practicing judo, rowing, pentathlon, volleyball, kayaking and biathlon, aged 16-33 years, were studied. Blood morphology indices: haemoglobin concentration (Hb), hematocrit (Hct), red blood cell count (RBC), leucocyte count (WBC), mean corpuscular haemoglobin concentration (MCHC), mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) were determined. The concentrations of ferritin, soluble transferrin receptor (sTfR) and iron, as well as total iron binding capacity (TIBC), were determined in serum. Additionally, erythropoietin (EPO) was assayed in subjects with elevated sTfR levels. Results: In no case iron-deficiency anaemia was found, but in 43% of subjects iron deficiency was detected. This included first stage of iron deficiency (iron depletion; ID) in 13% of subjects (ferritin <20 µg/L), and iron-deficient erythropoiesis (IDE) in 30% of subjects (ferritin <16 µg/L and sTfR> 2.75 mg/L). In all subjects with IDE, the concentrations of EPO were within normal range. The haematological indices remained unaffected in iron-depleted subjects, but in iron-deficient erythropoiesis subgroups the mean values of haemoglobin concentration and hematocrit were significantly lower than in subjects with normal iron stores (NIS). Conclusion: Despite the lack of anaemia among studied athletes, the incidence of latent iron deficiencies (iron depletion and iron-deficient erythropoiesis) was very high. The increasing incidence of iron deficiency, together with apparent decreases of haematological indices in subjects with iron-deficient erythropoiesis, markedly augments the risk of anaemia in young, competitive male athletes. Therefore, that category of subjects should be periodically screened for iron deficiency.